2012
DOI: 10.1155/2012/784364
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Multiple Sclerosis Disease-Modifying Therapies: A Systematic Review of the Literature

Abstract: Objective. To provide a current and comprehensive understanding of the cost-effectiveness of DMTs for the treatment of MS by quantitatively evaluating the quality of recent cost-effectiveness studies and exploring how the field has progressed from past recommendations. Methods. We assessed the quality of studies that met our systematic literature search criteria using the Quality of Health Economic Studies validated instrument. Results. Of the 82 studies that met our initial search criteria, we included 22 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 86 publications
(326 reference statements)
2
27
0
1
Order By: Relevance
“…On the basis of title and abstract, 966 records were excluded and the remaining 57 records were included for full-text screening. A further 48 articles were excluded at the full-text stage, leaving nine systematic reviews, [245][246][247][248][249][250][251][252][253] of which eight were economic evaluation studies [245][246][247][248][249][250][251][252] and one was a systematic review of studies that used a generic tool to measure HRQoL in people with multiple sclerosis. 253 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of title and abstract, 966 records were excluded and the remaining 57 records were included for full-text screening. A further 48 articles were excluded at the full-text stage, leaving nine systematic reviews, [245][246][247][248][249][250][251][252][253] of which eight were economic evaluation studies [245][246][247][248][249][250][251][252] and one was a systematic review of studies that used a generic tool to measure HRQoL in people with multiple sclerosis. 253 …”
Section: Resultsmentioning
confidence: 99%
“…First, most studies were unclear on whether study selection and data extraction were carried out in duplicate or did not carry out study selection and data extraction in duplicate. Second, although some authors [245][246][247][248][249][250][251]253 provided a list of included studies, not all of these authors 246,[248][249][250]253 provided a list of excluded studies. Third, it was unclear or not stated whether some authors assessed and/or documented the scientific quality of the included studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[37][38][39] One cost-effectiveness study found that the cost to prevent an MS relapse exceeded $80,000 for several IFNs and glatiramer acetate. 40 Dramatic increases in the cost of MS DMTs without significant improvements in efficacy will only further reduce the cost-effectiveness of these drugs.…”
Section: -25mentioning
confidence: 99%
“…They identified issues concerning the wide variation in costs and outcomes from different sources, from potentially unrepresentative samples, and the modeling of disease progression from natural history data from over 30 years ago. Yamamoto and Campbell [10] evaluated the quality of recent cost-effectiveness studies. They included 22 articles in their review and found that most studies (68%) achieved the highest quality category.…”
Section: Introductionmentioning
confidence: 99%